Attenuation Characteristics of Tuned Mass Dampers and Particle Tuned Mass Dampers in SDOF and MDOF Structures: Experimental Investigation and Simulation Analysis - Prashant Sunagar; Manish S. Dharek; Manjunatha M; Ranjitha Tangadagi B; Sifatullah Bahij (Advances in Civil Engineering, 2025)
This research article investigates the attenuation characteristics of passive control devices, viz., particle tuned mass damper (PTMD) and tuned mass damper (TMD) are used for a single degree of freedom (SDOF) and multidegree of freedom (MDOF) structure. Numerous parameters, like filling ratio, auxiliary mass ratio, particle density, and so on are pretending attenuation characteristics of particle damper. Recent research in the field of dynamics has explored enhanced characteristics of particle dampers toward attenuation of time history responses using both tuning of natural frequency and energy dissipation generated due to impact between particles and between particles and the container. TMD works in many cases as a simple pendulum and has not been found to attenuate the time history response of different earthquakes concentrating over contrasting frequencies. It works well when the earthquake concentrates its’ frequency near the damper frequency. However, PTMD works well during earthquakes, focusing on varying frequencies. An SDOF and MDOF structure generates a time history response subjected to standard earthquakes and sinusoidal waves using the shake table test results under damping from passive control devices. Also, a simulation model using SAP2000 has been established to discover the time history responses generated by TMD and PTMD. PTMD was more effective than TMD for SDOF and MDOF systems of structure in all cases of waveforms. However, TMD was more effective for the sine wave input waveform in the case of MDOF, as seen from the experimental and simulation studies.